2018
DOI: 10.3389/fcimb.2018.00181
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Activation Marker Neopterin: A Candidate Biomarker for Treatment Response and Relapse in Visceral Leishmaniasis

Abstract: The Leishmania parasite resides and replicates within host macrophages during visceral leishmaniasis (VL). This study aimed to evaluate neopterin, a marker of macrophage activation, as possible pharmacodynamic biomarker to monitor VL treatment response and to predict long-term clinical relapse of VL. Following informed consent, 497 plasma samples were collected from East-African VL patients receiving a 28-day miltefosine monotherapy (48 patients) or 11-day combination therapy of miltefosine and liposomal ampho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The importance of restoring the host immunity in VL is particularly demonstrated in immunosuppressed patients, such as those who are coinfected with human immunodeficiency virus (HIV), where VL is even more challenging to treat and results in more episodes of relapse and even death (58). Furthermore, neopterin, a Th1 immune marker, has been recently evaluated in VL patients after treatment with miltefosine alone or in combination with amphotericin B (59). Neopterin is exclusively produced by macrophages, which are activated by IFN-ɣ upon treatment (60, 61).…”
Section: Resultsmentioning
confidence: 99%
“…The importance of restoring the host immunity in VL is particularly demonstrated in immunosuppressed patients, such as those who are coinfected with human immunodeficiency virus (HIV), where VL is even more challenging to treat and results in more episodes of relapse and even death (58). Furthermore, neopterin, a Th1 immune marker, has been recently evaluated in VL patients after treatment with miltefosine alone or in combination with amphotericin B (59). Neopterin is exclusively produced by macrophages, which are activated by IFN-ɣ upon treatment (60, 61).…”
Section: Resultsmentioning
confidence: 99%
“…These results confirmed the findings in 20 VL patients by Schriefer and coworkers (Schriefer et al, 1995). Likewise, Kip and coworkers recently confirmed the pharmacodynamic potential of neopterin to identify Sudanese and Kenyan VL patients at risk for VL relapse (Kip et al, 2018). Unfortunately, the longitudinal evaluation of neopterin in coinfected patients has not yet been reported.…”
Section: Discussionmentioning
confidence: 89%
“…This study showed a dramatic change in the inflammatory cytokines during the 7 days after the start of therapy. Few studies have evaluated the biomarkers of response as early as this time 12 . At seven days, the concentrations of IL‐6, IL‐10 and IL‐8 were the best biomarkers of the early response, followed by the platelet and white blood cells counts.…”
Section: Discussionmentioning
confidence: 99%
“…In their systematic review, Kip et al 12 revealed few studies for the biomarkers of response as early as seven days or less. Wasunna et al 13 evaluated CRP and other acute‐phase reactants as early markers, even before seven days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation